Korelasi Antara ASI dengan Sperma Sebagai Faktor Penyebab Mahramiyah Susuan - Lawang, Karimuddin Abdullah; A. Rahman, Maimun; Nur, Syamsiah; Azhar, Muh. Zaim; Suage, Ali (Institut Agama Islam Negeri Curup, 2023)
This paper aims to answer the question of why breast milk can cause mahramiyah of breastfeeding in the same way as sperm can cause mahramiyah of nasab. Breast milk is food for babies that serves to grow flesh and strengthen bones. On the other hand, breast milk is a liquid that comes out of the human body, similar to blood. However, breastfeeding a baby who has not reached the age of two years can cause mahramiyah, which is the same as mahramiyah caused by sperm. This is different from blood transfusions, which do not have any legal consequences. The research method used is a descriptive qualitative research method. The data collection technique is documentation review sourced from classical literature and scientific journals. After the data is collected, it is analyzed using content analysis techniques. The results show that breast milk has a correlation with sperm so that it can cause a mahramiyah relationship to be established. This is because breast milk contains genes as found in sperm, so that the genes owned by the mother will be inherited to the child when she is breastfed. The similarity of the inherited genes is what causes a negative impact on offspring in the event of marriage, so Islam states that there is a mahramiyah relationship from breastfeeding.